Dinamika Ruang Ekonomi Politik : (Studi Tentang Pembangunan Jogging Track di Wilayah Kawasan Sempadan Pesisir Kelapa Lima Kota Kupang) - Wanda Kristina Pono; Yeftha Yerianto Sabaat; Stefanus Triadmaja Bria (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to explain the dynamics of political economic space in the development of jogging tracks in the coastal border area of Kelapa Lima, Kupang City. In line with research, this research uses descriptive qualitative, in qualitative research using data collection techniques in the form of observation, documentation, and interviews from several informants. The author sees that the problem of building a jogging track in the coastal border area of Kelapa Lima is experiencing resistance from the surrounding community, therefore the author wants to dig deeper into the problems that occur in building a jogging track in the coastal border area of Kelapa Lima. From the research results, it can be concluded that the spatial practice indicators that occur cause local communities to be eliminated from that space, while the spatial representation indicators do not match what the community expects and the spatial representation indicators only benefit the government. Government domination causes people in coastal areas to experience cultural subjugation, just as government domination causes people to be eliminated.